The Effect of Training on Job Satisfaction of Financial Staff of Indonesian Ursuline Education Foundation Mediated by Performance - Praksedes Gustanda (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In a world situation that is changing so fast, complex, ambiguous, and uncertain which causes intense competition in various fields, the quality of human resources becomes a determinant of an organization's competitive advantage. This quantitative study aims to examine the effect of training on job satisfaction mediating by performance. 80 financial staff of the Indonesian Ursuline Education Foundation participated in this study as respondents. Data was collected through google form and analyzed using SSPS for windows. The results showed that there was a positive and significant effect of performance on job satisfaction and a positive and significant effect of training on performance. Therefore, it is important for the Ursuline Education foundation to enrich the knowledge and skills of financial staff with training as it can improve performance and subsequently have a major impact on job satisfaction.